PREDICTION OF PROMISCUOUS EPITOPE STUDIES OF SPA ANTIGEN IN STAPHYLOCOCCUS AUREUS: AN INSIGHT ON PEPTIDE-BASED VACCINE - Zaveri, Kunal; Patnala, Kiranmayi (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Owing to the difficulty in providing drug therapies against Methicillin-resistant Staphylococcus aureus (MRSA), the development of an effective and promising vaccine is an immense challenge in combatingMRSA infections. The present work focuses on the development of a peptide-based vaccine, by identifying the epitopes from SPA antigen. Methods: The epitopes were identified based on different properties, such that they are capable of eliciting broadly neutralizing immune responses. The identified epitopes were subjected for peptide docking using Glide and antibody-antigen docking using ClusPro. Results: By in silico approach two epitopes NLNEEQRNGâ€ and LKDDPSQSANâ€ were identified for SPA protein with sequence lengths of nine and ten respectively. The least energy for the peptide docking was observed for NLNEEQRNG sequence and the amino acid residues of this peptide share similar interaction with antibody-antigen docking. Conclusion: Based on the properties and docking studies the best-ranked epitope sequence is â€˜NLNEEQRNG'. Further studies on this peptide sequence might be helpful for alternative therapy of MRSA infections. Keywords: Epitope, SPA antigen, IgG antibody, Docking studies